Neoadjuvant Chemotherapy in Nasopharyngeal Carcinoma - Sabeeh Al-Rawaq, Khudair J. (Journal of the Faculty of Medicine Baghdad, 2012)
Back ground: nasopharyngeal carcinoma is rare in Iraq and the treatment of this tumor is usually by radiotherapy and chemotherapy.Objectives: this study was conducted to estimate the effect of neoadjuvant chemotherapy in Iraqi patients with nasopharyngeal carcinomaPatients and methods: This study included sixty patients already diagnosed with nasopharyngeal tumors who attended the department of oncology in Baghdad teaching hospital during the period from January 2009 to December 2010,50 patients of them were treated by using combination chemotherapy in the form of Paclitaxel,5Flurouracil and cisplatinol for 4 courses prior to radiotherapy. Neoadjuvant chemotherapy was given due to advanced stage at presentation and due to long waiting list for radiotherapy which takes at least 6 months.10 patients were excluded from the study due to different reasons.Results: About half of the patients had partial response to neoadjuvant chemotherapy,only 8 patients (16%) had complete response, 12 patients (24%) did not show any response and 5 patients (10%) have progressive disease during the course of neo adjuvant chemotherapy.Conclusion: Neoadjuvant chemotherapy is beneficial in the management of Nasopharyngeal Cancer regarding local control and overall response rate.